Extracorporeal membrane oxygenation as rescue therapy in a pediatric liver transplant recipient with very severe hepatopulmonary syndrome. (6th November 2021) - Huang, Joy; Yoeli, Dor; Sundaram, Shikha S; Carpenter, Todd; Annam, Aparna; Pahlavan, Sheila; Wachs, Michael; Adams, Megan A.
Abstract: Background: In children with cirrhosis, the prevalence of HPS ranges from 3% to 20%, resulting in impaired gas exchange due to alterations in pulmonary microvasculature. LT is the gold‐standard cure for cirrhosis complicated by HPS and should ideally be performed prior to the development of severe HPS due to increased risk for post‐transplant hypoxia, right heart failure, and outflow obstruction. Methods: We present a case of a 13‐year‐old man, who underwent pediatric LT for severe HPS complicated by postoperative respiratory collapse, requiring a 92‐day course of veno‐venous ECMO. Results: Post‐transplant, despite BiPAP, inhaled nitric oxide and isoproterenol infusion, he remained hypoxic postoperatively and acutely decompensated on postoperative day 25, requiring veno‐venous ECMO. After 84 days on ECMO, a persistent large splenorenal shunt was identified that was embolized by interventional radiology, and 8 days after shunt embolization and ASD closure, he was successfully weaned off ECMO. Conclusions: This case describes the longest known duration of ECMO in a pediatric LT recipient and a unique improvement in hypoxemia following a portosystemic shunt closure. ECMO presents a heroic rescue measure for pediatric LT recipients with HPS that develops acute respiratory failure postoperatively refractory to alternative measures.